2016
DOI: 10.5127/pr.045616
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Negative Thinking in Social Anxiety Disorder 2: Post-Event Processing

Abstract: Cognitive models of social anxiety disorder (SAD) emphasize post-event processing as a prominent maintaining factor that occurs after social-evaluative events. Post-event processing involves repetitive negative thinking revolved around perceived social failure. The present review concentrates on the relevant and available empirical literature on post-event processing in social anxiety which centres on Clarke and Wells (1995) theoretical framework. Correlational and experimental studies have investigated the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…In terms of similarities, both AP and PEP are processes that are considered repetitive, negatively valenced, centered on social performance, and difficult to disengage from (Laposa & Rector, 2016). Conversely, there also appears to be functional differences between them that support their diagnostic specificity (for a review of AP, see Sluis, Boschen, Neumann, & Murphy, 2017a; for a review of PEP, see Brozovich & Heimberg, 2008; Sluis, Boschen, Neumann, & Murphy, 2017b; Wong, 2016). The most distinct differences between AP and PEP include temporal orientation (i.e., prior to an event and post-event) and discrepancy (i.e., a completed vs. an uncompleted task; Martin & Tesser, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of similarities, both AP and PEP are processes that are considered repetitive, negatively valenced, centered on social performance, and difficult to disengage from (Laposa & Rector, 2016). Conversely, there also appears to be functional differences between them that support their diagnostic specificity (for a review of AP, see Sluis, Boschen, Neumann, & Murphy, 2017a; for a review of PEP, see Brozovich & Heimberg, 2008; Sluis, Boschen, Neumann, & Murphy, 2017b; Wong, 2016). The most distinct differences between AP and PEP include temporal orientation (i.e., prior to an event and post-event) and discrepancy (i.e., a completed vs. an uncompleted task; Martin & Tesser, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the relationship between social anxiety and problematic cannabis use also support this hypothesis. For example, Ecker and Buckner (2017, 2018) suggest that postevent ruminations are an important process for understanding the link between social anxiety and problematic cannabis use, and it has been suggested that a high tendency to be self‐focused is responsible for the emergence of postevent processing (Sluis et al, 2017). Therefore, self‐focused attention is probably an important process in the development and maintenance of problematic cannabis use in socially anxious people.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have also found a positive association between cannabis use or related problems and RNT (du Pont et al, 2018; Ecker & Buckner, 2017, 2018). For example, Ecker and Buckner (2017, 2018) showed that postevent processing, a specific form of RNT about social situations implicated in the development and maintenance of social anxiety (Sluis et al, 2017), was positively associated cross‐sectionally with cannabis‐related problem severity and experimentally with cannabis use frequency. Overall, these data suggest that different forms of RNT could be a risk factor for problematic cannabis use, although the data are limited.…”
Section: Introductionmentioning
confidence: 99%